Pengembangan dan Pelatihan Pengelolaan Situs Web UMKM Shofi Cookies - Dedy Sugiarto; Ratna Shofiati; Syandra Sari; Muhamad Ichsan Gunawan; Ridho Rachmat Giffary; Ida Jubaidah; Azhar Rizki Zulma (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Shofi Group is a business engaged in cake production which was founded by the late Guswan Zainal, the husband of umi Nyi mas Yusnaini who was awarded the Capital City Award. The problem found is the absence of a website to introduce its products more broadly to all regions of Indonesia and abroad. The purpose of this activity is to develop a marketing website for the Shofi Group and provide training on website management. website development for SMEs Shofi Group uses the System Development Life Cycle (SDLC) approach. The series of activities began with two meetings with SME owners discussing the needs of web development followed by website creation and ended with training on Sunday, June 26, 2022. The Shofi Cookies MSME Website Management Training activity which was responded with excellent results was attended by a representative of Shofi group as web admin.